A Topology Analysis-Based MMC-HVDC Grid Transmission Capacity Calculation Method - Xiao Yu (Symmetry, 2021)
Modular multilevel converter-based high voltage direct current (MMC-HVDC) has a broad application prospect in renewable energy transmission. With the development of converter capacity, the transmission capacity calculation for MMC-HVDC grids becomes important for power dispatching. The existing method depends on manual work and is suitable for a simple grid. However, as the grid structure and operation modes become more and more complex, it becomes difficult to calculate the transmission capacity of different operation modes for an MMC-HVDC grid. This paper analyzed and simplified affecting factors and basic topologies. On this basis, a topology-based MMC-HVDC grid transmission capacity calculation method is proposed. First, an MMC-HVDC grid is divided into sending end grid, transmission section lines, and receiving end grid. Then the power limits of these three parts are calculated. Finally, the transmission capacity is determined by analyzing the connection mode of these three parts. This method can be adapted to any kind of MMC-HVDC grid and can be easily programmed.